Иллюстрация в детских журналах царской России [Pictures in Children’s Literature Journals of Czarist Russia] - Gubergits, Anna (Slavica Revalensia, 2015)
This article is an overview of the history of Russian illustrated journals for children. It covers the period from the 1860s to the beginning of 20th century, and addresses the problem of how the journal Rodnik (Spring) competed with Tropinka (Path). These journals strived to attract the most famous writers, poets, and graphic artists, yet did not survive competition with inexpensive children’s books: Tropinka came to an end in 1912, while Rodnik ceased production four years later.